Peanut stripe potyvirus: Prevalence, detection and serological relationships - and A. VARMA, R.K. JAIN*, I. LAHIRI (Indian Phytopathology, 2002)
Peanut stripe potyvirus (PStV) has been prevalent in five major peanut [groundnut] growing states of India: Andhra Pradesh, Gujarat, Karnataka, Maharashtra and Tamil Nadu. Surveys conducted over a 3-year period (1992-94) revealed its prevalence in two more states, Rajasthan and Uttar Pradesh. Direct antigen-coated enzyme-linked immunosorbent assay (DAC-ELISA) and immunosorbent electron microscopy (ISEM) were used to detect PStV in groundnut plants collected from these states. While PStV was detected in the majority of symptomatic plants, a significant proportion (31%) of asymptomatic plants were also PStV positive. PStV could not be detected in roots and seeds from PStV-positive plants. The virus was unevenly distributed in infected plants. Composite sampling comprising of quadrifoliates of different ages from the main axis and lateral branches is thus suggested for accomplishing reliable detection. The PStV isolate used in this study was serologically related to cowpea aphid-borne mosaic (CABMV)and soybean mosaic (SbMV) potyviruses.